Forest ecological research in the perspective of mitigating climate change in tropical ecosystem: case study of Cameroon (Central Africa) - Sonwa, D.J.; Tchienkoua, M. (2009)
There is a growing recognition that climate change is an important issue that impact adversely people livelihood and sustainable development Mitigating climate change through afforestation, reforestation and reducing emissions from deforestation and forests degradation (REDD) can become key components of land use planning and land use management in several tropical countries. Challenges in most countries include the design and implementation of sound research programs that satisfy the information needs of a national and international agenda on climate change. In the perspective of guiding forest-related research activities associated with climate change mitigation, this review synthesizes past research activities and provides baseline orientation for ecological research oriented towards climate change mitigation in Cameroon. The ecological and socioeconomic diversity offered by the country offers great opportunities for pilot mitigation research initiatives that can be extrapolated in other parts of central African sub region. However there is a need for enhanced research infrastructure, financial resources and capacity building in order to ensure continuous production of new scientific information